GIS-Based Land Suitability and Crop Vulnerability Assessment under Climate Change in Chtouka Ait Baha, Morocco - Marieme Seif-Ennasr; Lhoussaine Bouchaou; Zine El Abidine El Morjani; Abdelaziz Hirich; El Hassane Beraaouz; Redouane Choukr-Allah (Atmosphere, 2020)
Agriculture plays a crucial role in the economic development in Morocco, contributing to 14% of the national gross domestic product. However, this sector is facing various challenges, including climate change. This study aims to assess relevant indicators that may affect land suitability, water demand, and crop growing season duration under climate change. Further, it may be used as a decision support tool in the Chtouka area known for its irrigated agriculture. The approach proposed, the spatial distribution of land based on suitability, is founded on the multiple-criteria decision-making method of four parameters; soil texture, temperature, land use, and slope. The duration of the length of crop season was simulated using the concept of growing degree days. The projection of land suitability for 2031–2050 indicated an important decrease of 12.11% of “highly suitable” agricultural land under the RCP4.5 emission scenario and a significant increase of 4.68% of “highly unsuitable” land, according to the RCP8.5 emission scenario compared to the baseline (1985–2005). The projected growing degree days in 2031–2050 showed a strong shortening in the growing period length compared to the baseline 1985–2006, mainly under the RCP8.5 emission scenario, with a reduction from 8% to 21% depending on crops. Moreover, crop water productivity indicated that berries were over 50% less water productive than other vegetable crops for almost the same amount of applied irrigation water. These findings highlight the vulnerability of agriculture to climate change, which requires important political and management efforts to sustain agricultural activity.